Consider all parabolas:
1.
![y = x^2 + 6x + 8,\\y=x^2+6x+9-9+8,\\y=(x^2+6x+9)-1,\\y=(x+3)^2-1.](https://tex.z-dn.net/?f=y%20%3D%20x%5E2%20%2B%206x%20%2B%208%2C%5C%5Cy%3Dx%5E2%2B6x%2B9-9%2B8%2C%5C%5Cy%3D%28x%5E2%2B6x%2B9%29-1%2C%5C%5Cy%3D%28x%2B3%29%5E2-1.)
When x=-3, y=-1, then the point (-3,-1) is vertex of this first parabola.
2.
![y = 2x^2 + 16x + 28=2(x^2+8x+14),\\y=2(x^2+8x+16-16+14),\\y=2((x^2+8x+16)-16+14),\\y=2((x+4)^2-2)=2(x+4)^2-4.](https://tex.z-dn.net/?f=y%20%3D%202x%5E2%20%2B%2016x%20%2B%2028%3D2%28x%5E2%2B8x%2B14%29%2C%5C%5Cy%3D2%28x%5E2%2B8x%2B16-16%2B14%29%2C%5C%5Cy%3D2%28%28x%5E2%2B8x%2B16%29-16%2B14%29%2C%5C%5Cy%3D2%28%28x%2B4%29%5E2-2%29%3D2%28x%2B4%29%5E2-4.)
When x=-4, y=-4, then the point (-4,-4) is vertex of this second parabola.
3.
![y =-x^2 + 5x + 14=-(x^2-5x-14),\\y=-(x^2-5x+\dfrac{25}{4}-\dfrac{25}{4}-14),\\y=-((x^2-5x+\dfrac{25}{4})-\dfrac{25}{4}-14),\\y=-((x-\dfrac{5}{2})^2-\dfrac{81}{4})=-(x-\dfrac{5}{2})^2+\dfrac{81}{4}.](https://tex.z-dn.net/?f=y%20%3D-x%5E2%20%2B%205x%20%2B%2014%3D-%28x%5E2-5x-14%29%2C%5C%5Cy%3D-%28x%5E2-5x%2B%5Cdfrac%7B25%7D%7B4%7D-%5Cdfrac%7B25%7D%7B4%7D-14%29%2C%5C%5Cy%3D-%28%28x%5E2-5x%2B%5Cdfrac%7B25%7D%7B4%7D%29-%5Cdfrac%7B25%7D%7B4%7D-14%29%2C%5C%5Cy%3D-%28%28x-%5Cdfrac%7B5%7D%7B2%7D%29%5E2-%5Cdfrac%7B81%7D%7B4%7D%29%3D-%28x-%5Cdfrac%7B5%7D%7B2%7D%29%5E2%2B%5Cdfrac%7B81%7D%7B4%7D.)
When x=2.5, y=20.25, then the point (2.5,20.25) is vertex of this third parabola.
4.
![y =-x^2 + 7x + 7=-(x^2-7x-7),\\y=-(x^2-7x+\dfrac{49}{4}-\dfrac{49}{4}-7),\\y=-((x^2-7x+\dfrac{49}{4})-\dfrac{49}{4}-7),\\y=-((x-\dfrac{7}{2})^2-\dfrac{77}{4})=-(x-\dfrac{7}{2})^2+\dfrac{77}{4}.](https://tex.z-dn.net/?f=y%20%3D-x%5E2%20%2B%207x%20%2B%207%3D-%28x%5E2-7x-7%29%2C%5C%5Cy%3D-%28x%5E2-7x%2B%5Cdfrac%7B49%7D%7B4%7D-%5Cdfrac%7B49%7D%7B4%7D-7%29%2C%5C%5Cy%3D-%28%28x%5E2-7x%2B%5Cdfrac%7B49%7D%7B4%7D%29-%5Cdfrac%7B49%7D%7B4%7D-7%29%2C%5C%5Cy%3D-%28%28x-%5Cdfrac%7B7%7D%7B2%7D%29%5E2-%5Cdfrac%7B77%7D%7B4%7D%29%3D-%28x-%5Cdfrac%7B7%7D%7B2%7D%29%5E2%2B%5Cdfrac%7B77%7D%7B4%7D.)
When x=3.5, y=19.25, then the point (3.5,19.25) is vertex of this fourth parabola.
5.
![y =2x^2 + 7x +5=2(x^2+\dfrac{7}{2}x+\dfrac{5}{2}),\\y=2(x^2+\dfrac{7}{2}x+\dfrac{49}{16}-\dfrac{49}{16}+\dfrac{5}{2}),\\y=2((x^2+\dfrac{7}{2}x+\dfrac{49}{16})-\dfrac{49}{16}+\dfrac{5}{2}),\\y=2((x+\dfrac{7}{4})^2-\dfrac{9}{16})=2(x+\dfrac{7}{4})^2-\dfrac{9}{8}.](https://tex.z-dn.net/?f=y%20%3D2x%5E2%20%2B%207x%20%2B5%3D2%28x%5E2%2B%5Cdfrac%7B7%7D%7B2%7Dx%2B%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D2%28x%5E2%2B%5Cdfrac%7B7%7D%7B2%7Dx%2B%5Cdfrac%7B49%7D%7B16%7D-%5Cdfrac%7B49%7D%7B16%7D%2B%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D2%28%28x%5E2%2B%5Cdfrac%7B7%7D%7B2%7Dx%2B%5Cdfrac%7B49%7D%7B16%7D%29-%5Cdfrac%7B49%7D%7B16%7D%2B%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D2%28%28x%2B%5Cdfrac%7B7%7D%7B4%7D%29%5E2-%5Cdfrac%7B9%7D%7B16%7D%29%3D2%28x%2B%5Cdfrac%7B7%7D%7B4%7D%29%5E2-%5Cdfrac%7B9%7D%7B8%7D.)
When x=-1.75, y=-1.125, then the point (-1.75,-1.125) is vertex of this fifth parabola.
6.
![y =-2x^2 + 8x +5=-2(x^2-4x-\dfrac{5}{2}),\\y=-2(x^2-4x+4-4-\dfrac{5}{2}),\\y=-2((x^2-4x+4)-4-\dfrac{5}{2}),\\y=-2((x-2)^2-\dfrac{13}{2})=-2(x-2)^2+13.](https://tex.z-dn.net/?f=y%20%3D-2x%5E2%20%2B%208x%20%2B5%3D-2%28x%5E2-4x-%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D-2%28x%5E2-4x%2B4-4-%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D-2%28%28x%5E2-4x%2B4%29-4-%5Cdfrac%7B5%7D%7B2%7D%29%2C%5C%5Cy%3D-2%28%28x-2%29%5E2-%5Cdfrac%7B13%7D%7B2%7D%29%3D-2%28x-2%29%5E2%2B13.)
When x=2, y=13, then the point (2,13) is vertex of this sixth parabola.